Optimal warm-up stimuli of muscle activation to enhance short and long-term acute jumping performance - de Villareal, E. S. S.; Gonzales-Badillo, J. J.; Izquierdo, M. (European Journal of Applied Physiology, 2007)
The aim of this study was to determine the effect of different types of active warm-up stimuli of muscle activation on explosive jumping performance after short (5 min postwarm-up) and long (6 h postwarm-up) recovery periods following warm-up. Twelve trained volleyball players (21-24 years) performed different types of specific warm-up stimuli (WP) after baseline measurements [e.g., countermovement jump (CMJ) without and with extra load and Drop jump (DJ)] on randomized separate occasions: (1) three sets of five jumps with extra load (WP1), (2) two sets of four reps at 80% of 1RM parallel squat (1RMPS) and two sets of two reps at 85% of 1RMPS (WP2), (3) two sets of four reps at 80% of 1RMPS and two sets of two reps at 90% of 1RMPS and two sets of one rep at 95% of 1RMPS (WP3), (4) three sets of five DJs (WP4), (5) specified warm-up for a volleyball match (WP5), (6) three sets of five reps at 30% 1RMPS (WP6), and (7) an experimental condition of no active warm-up. Height in DJ significantly improved (P < 0.05) after WP1 (4.18%), WP2 (2.98%), WP3 (5.47%), and WP5 (4.49%). Maximal power output during CMJ with extra load significantly improved (P < 0.05) after WP2 (11.39%), WP5 (10.90%), WP3 (9%), and WP1 (2.47%). High-intensity dynamic loading (e.g., 80-95% 1RM), as well as specific volleyball warm-up protocol bring about the greatest effects on subsequent neuromuscular explosive responses. Acute positive effects on jumping performance after warm-up were maintained after long recovery periods (e.g., 6 h following warm-up), particularly when prior high-intensity dynamic actions were performed.